2004
DOI: 10.1063/1.1815053
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of carbon nanotubes with single-molecule fluorescence microscopy

Abstract: Single walled carbon nanotubes (SWNTs) are a promising gene and drug delivery system since their physical dimensions mimic nucleic acids. Towards this aim, the hydrophobicity of SWNTs was averted by coating with ribonucleic acid (RNA) polymer [poly(rU)] or bovine serum albumin (BSA) and the consequent diffusion of these synthetic-biomolecular hybrids was studied by single-molecule fluorescence microscopy. The diffusion coefficient for SWNT-poly(rU) was measured at 0.374±0.045μm2∕s and for SWNT-BSA it was 0.442… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Ke et al [41][42][43] described spectral properties of RNA bound to SWNTs as well as RNA polymer translocation with SWNTs. Our interest is to construct assembled thin film of gene polymers RNA-SWNT nanocomposites on a solid substrate by using the so-called ''layer-by-layer deposition'' technique is possible [44].…”
Section: Rna-swnts Thin Filmsmentioning
confidence: 98%
“…Ke et al [41][42][43] described spectral properties of RNA bound to SWNTs as well as RNA polymer translocation with SWNTs. Our interest is to construct assembled thin film of gene polymers RNA-SWNT nanocomposites on a solid substrate by using the so-called ''layer-by-layer deposition'' technique is possible [44].…”
Section: Rna-swnts Thin Filmsmentioning
confidence: 98%
“…Carbon nanotubes are characterized in terms of diffusion by single molecule fluorescent microscopy. 26) These synthetic carriers were found to be biocompatible when studied on human HEK 293 cells, signifying their safety. 27) Multiwalled carbon nanotubes are also suitable delivery system for transformation specifically to bacterial cells (E. coli) and for nanoscale cell electroporation.…”
Section: )mentioning
confidence: 99%
“…[1] Recent reports have demonstrated that CNTs can also be wrapped with RNA oligonucleotides in the same way as short oligos of DNA. [2] Single molecules of poly(rU)-CNT (U: uracil) composites have been used to visualize CNTs using RNA fluorescent dyes [3] and were shown to be transported inside living cells with potential applications in drug delivery. [4] RNAwrapped CNTs have several potential advantages over DNAwrapped tubes for biomedical applications.…”
mentioning
confidence: 99%